Cold‐sensitive phenotypes of a yeast null mutant of ARV1 support its role as a GPI flippase. Issue 15 (11th June 2020) - Okai, Haruka; Ikema, Ryoko; Nakamura, Hiroki; Kato, Mei; Araki, Misako; Mizuno, Ayumi; Ikeda, Atsuko; Renbaum, Paul; Segel, Reeval; Funato, Kouichi
Abstract : Glycosylphosphatidylinositol (GPI) is synthesized in the endoplasmic reticulum (ER) and added onto proteins to form GPI‐anchored proteins. Among the many proteins involved in this process, ACAT‐related enzyme‐2 required for viability 1 (Arv1) is a candidate, functioning as a flippase that translocates GPI intermediates from the cytoplasmic side into the luminal side of the ER membranes. Here, we show that the deletion of the ARV1 gene in yeast leads to cold‐sensitive defects in cell growth and GPI anchor synthesis. Furthermore, complementation assays show that the overexpression of a missense human ARV1 ‐G189R mutant does not completely restore the cold‐sensitive phenotypes of the yeast arv1 mutant. Our results support the proposed role of Arv1 in GPI anchor synthesis and suggest that ARV1 ‐linked human diseases result from defective GPI anchor synthesis. Abstract :